EFEKTIVITAS PENGELOLAAN ZAKAT, INFAQ, SHADAQAH (ZIS) BAZDA UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT DI JAWA TENGAH - Heru Sulistyo; Budhi Cahyono; Sri Aniek (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
Zakat, infaq, and sadaqah (ZIS) potency is very large in Central Java as the instruments for reducing poverty and improving the community welfare. This study aims to assess the effectiveness of management ZIS as optimal as posible, so can give significant contribution to poverty reduction and welfare improvement. The law No. 23 of 2011 concerning the management of zakat has given a very strong legal foundation in the management of zakat, by collecting, distributing, and accountability. The unit of analysis in this study is Bazda in Central Java Province. The sample take from four districts/cities: Semarang city, Jepara regency, Demak regency, and the regency of Semarang. While the respondents were administrators Bazda, muzzaki, and mustahik in four regency/cities. The results showed that all Bazda (Semarang, Semarang regency, Demak, dan Jepara) already have data on muzzaki and mustahik, but does not have a data base mustahik and muzakis completely, so it can not be done for mapping the distribution of ZIS effectively and efficiently. The condition of the building, infrastructure and operational funds sourced budget has not been able to support the operations and performance of the collection, distributor and reporting effectively and efficiently. Distribution and utilization of ZIS dominated by the fulfillment of consumer needs and its focused on the areas of health, education and social empowerment, but for productive business activities still relative small, so it requires a paradigm shift in the management of the ZIS to make mustahik be muzzaki. Reporting and accountability system so far has been done transparent and accountable through a written report to the District / City Government and Parliament, but some Bazda not convey to mustahik in detail, both in book report and through the WEB. Only Jepara regency that has reporting system complete, organized, detailed and printed in book report to be sent to the regency government, parliament, muzakis, and the other institution. To realize effectiveness, BAZDA must have data based of muzzaki and mustahiq, and support by representative office, so the amil can do better. Coordination function must be develop with regional government, state ownership corporate, and private corporate to ensure of increase revenue of BAZDA, and to ensure amount of muzzaki.